Building Vocabulary for Language Learning: Approach for ESL Learners to Study New Vocabulary - Alharbi, Adel M. (Journal of International Students, 2015)
This project investigated Vocabulary Learning Strategies (VLSs) English Language Learners used; and strategies they thought were effective to them in terms of language proficiency. Using an online survey, 121 participants responded to statements regarding their usage of VLSs. Participants have been divided into two groups: (1) learners with low English proficiency level and (2) learners with high English proficiency level to measure the significance between them in response to the VLS questionnaire. The analysis measured five sets of vocabulary knowledge: building synonyms network, learning definition(s) with contexts, pronunciation process, bookmark word search, and remembering strategy for writing. This project determined that the group with high language proficiency agreed more on the items selected than those with low language proficiency.